THE EFFECT OF TOURIST INVOLVEMENT AND SERVICE QUALITY ON LOYALTY THROUGH THE CREATION OF SHARED VALUE - Sinambela, Fitriana Aidnilla; Stevani, Stevani; Fahlevi, Renza (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2026)
This study aimed to analyze the effects of tourist involvement and service quality on the loyalty of historical tourism visitors in Batam City, with shared value creation as a mediating variable. The study was motivated by the low interest in historical tourism despite Batam’s potential historical attractions, such as Kampung Vietnam and the Raja Ali Haji Museum. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The sample consisted of 120 respondents obtained through online questionnaires distributed to tourists who had visited historical tourism sites in Batam. The results indicate that tourist involvement and service quality have significant positive effects on shared value creation, which in turn has a positive impact on visitor loyalty. Furthermore, shared value creation mediates the relationship between tourist involvement and service quality on loyalty. These findings suggest that enhancing service quality and encouraging tourist involvement are essential strategies for building loyalty in historical tourism destinations.